Prevalence of Postpartum Anxiety and Depression after Intrapartum Oxytocin - Grace Valentine; I Putu G Kayika (Indonesian Journal of Obstetrics and Gynecology, 2016)
Objective: To know the prevalence of postpartum anxiety and depression in patients who received intrapartum oxytocin. Method: Across-sectional observational study was conducted in Dr. Cipto Mangunkusumo hospital. Observation used Edinburgh Postnatal Depression scale and Beck Anxiety Inventory before delivery day, on the first and fourteenth day of postpartum. Result: Of 112 patients, we found the prevalence of mild and moderate anxiety were 94.6% and 5.4%. There were no anxiety women before delivery and on the first day of postpartum. The prevalence of mild and moderate anxiety on the fourteenth day of postpartum were 83% and 16.9%. There was no severe anxiety found at those time. On the other hand, the prevalence of postpartum depression on the first and fourteenth day of postpartum were 31.3% and 32.1%. There was no association between exogenous oxytocin and postpartum anxiety also depression. In multivariate analysis, we found that women with low self image were more prone to postpartum anxiety (OR 0.16, 95% CI 0.06-0.46). Meanwhile, postpartum depression was associated significantly to self image (OR 0.17, 95% CI 0.07-0.83), low income (OR 10.35, 95% CI 1.72-62.45) and pregnancy plan (OR 0.17, 95% CI 0.06-0.53) Conclusion: The patients who received intrapartum oxytocin are more prevalent to have mild anxiety. The prevalence of depression before delivery day, on the first and fourteenth day of postpartum are similar. In statistic, there is no relationship between intrapartum oxytocin administration and postpartum anxiety or depression. [Indones J Obstet Gynecol 2016; 4-2: 59-63] Keywords: anxiety, depression, oxytocin intrapartum, postpartum